STA108: Statistics and Probability - UiTM, College of Computing, Informatics and Mathematics (2023)
This course introduces the basic knowledge of statistics and probability, and is divided into five topics; introduction to statistics, descriptive statistics, correlation and regression, introduction to probability and probability distributions. Applications to more general everyday problems towards science and technology will be included in order to provide a broader spectrum to the students and at the same time, develop their interest in the course. Students will be exposed to data analysis and interpretation of statistical software output. They will also have the experience of reporting and presenting the findings on statistical data analysis using the knowledge they have learnt in this course.